Speeding up parallel tempering simulations - Hasenbusch, Martin; Schaefer, Stefan (Physical review. E, Statistical, nonlinear, and soft matter physics, 2010)
We discuss methods that allow us to increase the step size in a parallel tempering simulation of statistical models and test them at the example of the three-dimensional Heisenberg spin glass. We find an overall speedup of about 2 for contemporary lattices.
Gesehen am 09.09.2022